(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the main and secondary themes of Isajon Sultan’s story “Yogoch Kovush”, the main idea of ​​the work. The historical method reveals the main theme of the story, and the comparative method explores the national and universal significance of the topic. The importance of the work in modern storytelling is noted. Although the story was based on the theme of the life and everyday life of foreign people, the idea of ​​the work was based on Eastern chastity, obedience and graceful relationships between father and daughter. Despite the fact that the hero father makes difficult demands on his daughter’s pride, he feels a sense of responsibility for his daughter, responsibility for her fate. This responsibility ruins the father’s life.